Potential of the predatory mite Amblydromalus zannoui to control pest mites on Jatropha curcas - Miranda, Valdirene Coutinho; de Azevedo, Emiliano Brandão [UNESP]; da Cruz, Wilton Pires; Jorge, Sofía Jiménez [UNESP]; Pedro-Neto, Marçal; de Campos Castilho, Raphael [UNESP]; Tixier, Marie-Stéphane; de Moraes, Gilberto José; Sarmento, Renato Almeida (Springer Nature, 2021)
Amblydromalus zannoui Sourassou, Sarmento and Moraes is a phytoseiid mite of the limonicus group described from central Brazil from leaves of physic nut, Jatropha curcas L. (Malpighiales: Euphorbiaceae), a plant potentially useful as a source of biofuel. This plant is often attacked by the mites Polyphagotarsonemus latus (Banks) (Prostigmata: Tarsonemidae) and Tetranychus bastosi Tuttle, Baker and Sales (Prostigmata: Tetranychidae). The objectives of this work were to evaluate the predation rate of A. zannoui on those phytophagous mites, to assess its life cycle on these prey and on pollen of Ricinus communis L. (Euphorbiaceae), and to determine its attraction to physic nut leaves infested by P. latus or T. bastosi. Amblydromalus zannoui attacked more nymphs and adults than eggs of P. latus, and more eggs and larvae than adults of T. bastosi. The life table parameters suggest that A. zannoui performs better on P. latus (rm: 0.20, Ro: 18.77; λ: 1.23) and pollen (rm: 0.18, Ro: 23.32, λ: 1.18). The predator seems to be attracted to plants with P. latus, but attraction was not clear cut for plants with T. bastosi. The results suggested that A. zannoui is a potential control agent to be used against P. latus on physic nut plants, and that R. communis pollen can be used as supplementary food to maintain the predator population in the absence of prey.
Keywords: Biological control; Castor bean pollen; Predator; Tarsonemidae; Tetranychidae